Manajemen Peningkatan Mutu Pendidikan Melalui Optimalisasi Supervisi Akademik Kepala SMPN 3 Palembang - Afriantoni; Enjelita, Anggi; Jannah, Nadia; Lantika, Vanezza Happy; Nuraini, Intan (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyse the management of educational quality improvement through the optimisation of academic supervision by the headteacher at SMP Negeri 3 Palembang. The study employs a qualitative approach with a descriptive design to gain an in-depth understanding of the planning, implementation and follow-up processes of academic supervision. The research subjects included the deputy headteacher for curriculum and subject teachers directly involved in supervision activities. Data collection was carried out through observation and in-depth interviews, followed by analysis using data reduction, data presentation, and conclusion drawing techniques, as well as triangulation to ensure data validity. The research findings indicate that academic supervision is carried out systematically through the stages of planning, implementation, monitoring, and follow-up. Supervision is conducted through classroom visits accompanied by constructive feedback and professional development for teachers. The optimisation of academic supervision contributes to the enhancement of teachers’ pedagogical competencies and the quality of the learning process, thereby effectively supporting the continuous improvement of educational quality.